2015
DOI: 10.1016/j.yjmcc.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Losartan treatment attenuates tumor-induced myocardial dysfunction

Abstract: Fatigue and muscle wasting are common symptoms experienced by cancer patients. Data from animal models demonstrate that angiotensin is involved in tumor-induced muscle wasting, and that tumor growth can independently affect myocardial function, which could contribute to fatigue in cancer patients. In clinical studies, inhibitors of angiotensin converting enzyme (ACE) can prevent the development of chemotherapy-induced cardiovascular dysfunction, suggesting a mechanistic role for the renin-angiotensin-aldostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 47 publications
(58 reference statements)
3
24
0
Order By: Relevance
“…Our cardiomyocyte data agrees with previous findings, indicating no change in the sarcomere percent peak shortening in the c26 adenocarcinoma model of cancer cachexia [6, 22]. There were significant decreases in TPS90 and TR90 in tumor-bearing mice compared to control, as the velocity was unchanged.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our cardiomyocyte data agrees with previous findings, indicating no change in the sarcomere percent peak shortening in the c26 adenocarcinoma model of cancer cachexia [6, 22]. There were significant decreases in TPS90 and TR90 in tumor-bearing mice compared to control, as the velocity was unchanged.…”
Section: Discussionsupporting
confidence: 92%
“…Heart function is notably depressed in this cancer model with reduced FS% and EF [6, 20, 22, 27]. This reduction in the FS% and EF is the result of thinning of the posterior wall during systole, causing chamber expansion and reducing blood ejection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, perindopril did not prevent the large decrease in cardiac ␣-myosin heavy chain mRNA expression in severely cachectic mice, which is typically associated with cardiac dysfunction (74). However, a recent study showed that the AT 1 antagonist losartan prevented the reductions in fractional shortening, ejection fraction, stroke volume, and posterior wall thickness and attenuated the increase in LV enddiastolic diameter during systole in C-26 tumor-bearing mice (102). Losartan treatment for 18 days also attenuated the decrease in systolic blood pressure and developed pressure and reduced tumor size in cachectic mice (102).…”
Section: Current Treatment Of Cardiac Atrophy In Cancer Cachexiamentioning
confidence: 94%
“…However, a recent study showed that the AT 1 antagonist losartan prevented the reductions in fractional shortening, ejection fraction, stroke volume, and posterior wall thickness and attenuated the increase in LV enddiastolic diameter during systole in C-26 tumor-bearing mice (102). Losartan treatment for 18 days also attenuated the decrease in systolic blood pressure and developed pressure and reduced tumor size in cachectic mice (102). The greater efficacy of AT 1 antagonism compared with ACE inhibition has important implications for the pathogenesis of cardiac cachexia in these preclinical models.…”
Section: Current Treatment Of Cardiac Atrophy In Cancer Cachexiamentioning
confidence: 97%